Tinjauan Yuridis Tanggung Jawab Rumah Sakit terhadap Kejadian Healthcare Associated Infections - Danang Sugihardana; Wardah Yuspin (Universitas Muhammadiyah Yogyakarta, 2024)
Health Care Associated Infections (HAIs) pose a serious concern in the global healthcare system, including in Indonesia. Hospitals bear significant legal responsibility regarding these infections in Indonesia. This study is a normative legal research aimed at analyzing and understanding all legal regulations related to the research topic. The objective is to comprehend the protection and accountability concerning cases of Healthcare Associated Infections in Indonesia. The findings of this research indicate that the provision of hospital services, as mandated by the Republic of Indonesia Law Number 44 of 2009 concerning Hospitals (UURS), plays a crucial role. In efforts to address and prevent the spread of HAIs, the Indonesian government has issued the Guidelines for the Prevention and Control of Infections in Health Service Facilities, namely the Minister of Health Regulation Number 27 of 2017. The legal responsibility of a hospital in criminal matters may fall upon the owner or director if linked to negligence in fulfilling their obligations. However, if all hospital obligations are carried out diligently, and all staff adheres to established rules and service standards, the hospital is usually not held criminally accountable in situations of nosocomial infections in patients.